Women Are Less Likely to Be Tested for HIV or Offered Preexposure Prophylaxis at the Time of Sexually Transmitted Infection Diagnosis. Issue 1 (January 2021) - Yumori, Caitlin; Zucker, Jason; Theodore, Deborah; Chang, Michelle; Carnevale, Caroline; Slowikowski, Jacek; LaSota, Elijah; Olender, Susan; Gordon, Peter; Cohall, Alwyn; Sobieszczyk, Magdalena E.
Abstract : Background: Ending the HIV epidemic requires linkage of at-risk individuals from diverse health care settings to comprehensive HIV prevention services. Sexually transmitted infections (STIs) are significant biomarkers of HIV risk and should trigger preexposure prophylaxis (PrEP) discussion. We reviewed STI testing practices outside of sexual health clinics to identify opportunities for improvement in the provision of HIV prevention services. Methods: An electronic sexual health dashboard was used to identify patient encounters with a positive gonorrhea, chlamydia, and/or rapid plasma reagin test result between January 1, 2019, and August 23, 2019, at a large urban academic medical center. A retrospective chart review was performed to assess HIV testing, completeness of STI screening, and HIV prevention discussion; inadequate screening was defined as no HIV test in 12 months before STI diagnosis. Results: A total of 815 patients with 856 patient encounters were included. Patients were predominantly female (64.4%); median age was 24 years (range, 18–85 years). The most common test and most common positive test result was the genitourinary gonorrhea/chlamydia nucleic acid amplification test. Multisite testing was rare (7.5% of patient encounters) and performed more frequently in men than in women (20.3% vs. 0.36%). Women were also more likely to be inadequately screened for HIV (15.1% vs. 25.8%). Documentation of PrEP discussion was rare (4.7% of patient encounters) compared with safe sex (44.6%) and condoms (49.8%). Preexposure prophylaxis was discussed almost exclusively with men compared with women (17% vs. 1.1%). Conclusions: In patients diagnosed with bacterial STI outside of sexual health clinics, gaps in HIV prevention exist. HIV screening, multisite STI screening, and discussion of PrEP were particularly infrequent among women. Abstract : In a retrospective chart review, women with bacterial sexually transmitted infections were less likely than men to receive HIV screening, multisite sexually transmitted infection screening, or preexposure prophylaxis discussion.